Qoraqalpoqlar etnologiyasi tarixiga doir (SCIENCE and SOCIETY, 2023)
The article reflects the features of ethnographic expeditions carried out in the Khorezm Oasis and Karakalpakstan be- fore and during the period of Independence. The analytical results are considered of the research work carried out by young ethnog- raphers in the years of independence.